The evolution of wound dressings: From traditional to smart dressings - Rezvani Ghomi, Erfan; Niazi, Mina; Ramakrishna, Seeram (Polymers for advanced technologies, 2023)
Wound healing has always been a great challenge throughout human history. Today, with a substantial rise in chronic diseases and surgical operations, there is more demand for wound dressings to facilitate the healing process. Modern dressings come in different forms and offer significant advantages over the traditionally used passive bandages by inhibiting microbial activity and providing a suitable moist environment for the wound. Despite their widespread clinical usage and successful results in wound treatment, even modern dressings cannot promote wound healing as expected since they are not responsive to the wound conditions. On the other hand, smart dressings can interact with the environment through their built‐in sensors and respond to wound needs. They can monitor the changes in wound healing stages and provide insightful information that could affect the treatment direction. The current manuscript reviews the evolution of wound dressings from ancient, traditional to modern dressings and presents the advanced class of smart dressings as the future trend in the field.